2019
DOI: 10.1177/0885328219825568
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and bone healing of Mg-Y-Zn-Zr-Ca alloy implants: Comparative in vivo study in a non-immobilized rat femoral fracture model

Abstract: Biodegradable magnesium (Mg) alloys exhibit improved mechanical properties compared to degradable polymers while degrading in vivo circumventing the complications of permanent metals, obviating the need for surgical removal. This study investigated the safety and efficacy of Mg-Y-Zn-Zr-Ca (WZ42) alloy compared to non-degradable Ti6Al4V over a 14-week follow-up implanted as pins to fix a full osteotomy in rat femurs and as wires wrapped around the outside of the femurs as a cerclage. We used a fully load bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…The selection of animal model was established following the published literature on testing Mg alloys which evaluate their biocompatibility and biodegradation in vivo behavior closer to this study [5][6][7][13][14][15]17,[19][20][21][22][23][24][25][26].…”
Section: Experimental Animals and Modelmentioning
confidence: 99%
“…The selection of animal model was established following the published literature on testing Mg alloys which evaluate their biocompatibility and biodegradation in vivo behavior closer to this study [5][6][7][13][14][15]17,[19][20][21][22][23][24][25][26].…”
Section: Experimental Animals and Modelmentioning
confidence: 99%
“…Mg-RE alloys were generally evaluated in vivo on small- to medium-size animal models. Chow et al [ 124 ] investigated the safety and efficacy of WZ42 magnesium alloy, compared to nondegradable Ti6Al4V, on SD rats. The implanted samples were intramedullary pins of 15 mm length × 1.66 mm diameter, used to fix a full osteotomy on femoral bone and wires of 20 mm length × 0.68 mm diameter, which were wrapped around the femur.…”
Section: Animal Testingmentioning
confidence: 99%
“…In addition to that, Zr generally has low toxicity 136 . Chou et al 137 . implanted WZ42 (Mg–4.0%Y–2.0%Zn–1.0%Zr–0.6%Ca in wt.%) alloy as wires rolled around the outside of the femurs as a cerclage and as pins to repair an osteotomy in rat femurs.…”
Section: Opportunities To Overcome the Current Challengesmentioning
confidence: 99%
“… 136 Chou et al. 137 implanted WZ42 (Mg–4.0%Y–2.0%Zn–1.0%Zr–0.6%Ca in wt.%) alloy as wires rolled around the outside of the femurs as a cerclage and as pins to repair an osteotomy in rat femurs. The results indicated that the WZ42 alloy could be a potential material for load‐bearing orthopedic applications because normal bone healing occurred in femurs fixed with the WZ42 alloy after 14 weeks of surgery, and no accumulation of magnesium, as well as alloying elements, was observed in the liver and kidney of rats.…”
Section: Opportunities To Overcome the Current Challengesmentioning
confidence: 99%